2000
DOI: 10.1080/00221320009596720
|View full text |Cite
|
Sign up to set email alerts
|

Shame, Self-Consciousness, and Locus of Control in People Who Stutter

Abstract: Stuttering is a multidimensional disorder, including psychological as well as physiological elements. This investigation of the value of 3 psychological constructs (shame, self-consciousness, and locus of control) in the prediction of 3 self-reported behavioral dimensions of stuttering (struggle, avoidance, and expectancy) revealed shame and self-consciousness to be significant psychological predictors of the selected dimensions of stuttering, whereas locus of control was found not to be. Certain demographic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…Whilst some studies have shown locus of control to predict treatment outcome (e.g. Andrews & Craig, 1988;Craig, Franklin, & Andrews, 1984), others have highlighted its limited utility and predictive value (De Nil & Kroll, 1995;Ginsberg, 2000;Ladouceur et al, 1989). A well-powered study (N = 78) by Block et al (2006) found locus of control did not predict long-term outcome, even though it was clearly independent of severity.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Whilst some studies have shown locus of control to predict treatment outcome (e.g. Andrews & Craig, 1988;Craig, Franklin, & Andrews, 1984), others have highlighted its limited utility and predictive value (De Nil & Kroll, 1995;Ginsberg, 2000;Ladouceur et al, 1989). A well-powered study (N = 78) by Block et al (2006) found locus of control did not predict long-term outcome, even though it was clearly independent of severity.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, people who stutter may experience avoidance, struggle, anxiety and embarrassment (Riley, Riley, & Maguire, 2004), as well as expectancies of social harm, fear of negative evaluation, social isolation, self-consciousness and poor self-esteem (Cream, Onslow, Packman, & Llewellyn, 2003;Ginsberg, 2000;Messenger, Onslow, Packman, & Menzies, 2004). In light of these negative consequences, there is growing awareness of the potential for stuttering to hinder normal social and psychological development (Craig, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…For example, persons who stutter may experience a negative impact of their disorder on school performance, in their relationships with teachers and classmates, as well as in their employment opportunities and job performance (Klein & Hood, 2004;Klompas & Ross, 2004). In addition to these negative social consequences, persons who stutter may experience frequently intense feelings of anxiety, shame, loss of control and avoidance (e.g., Corcoran & Stewart, 1998;Ginsberg, 2000;Messenger, Onslow, Packman, & Menzies, 2004;Tran, Blumgart, & Craig, 2011). For these reasons, it is increasingly important for clinicians and researchers to consider these negative social as well as psychological consequences in the assessment and treatment of individuals who stutter (e.g., Craig et al, 2009;Cummins, 2010;Franic & Bothe, 2008;Guntupalli, Kalinowski, & Saltuklaroglu, 2006;Yaruss, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…People who stutter express a vast array of psychological experiences associated with stuttering, including reports of challenge, triumph, and heartache (Ginsberg, 2000). Conture (2001), Conture (2004) and Conture, Walden, Arnold, Graham, and Karass (in press) believe that the psychosocial processes of people who stutter are complexly related to their speech production behavior.…”
Section: Introductionmentioning
confidence: 98%